PEMBUATAN VELVA SAYURAN ( KAJIAN PROPORSI WORTEL, TOMAT, KECAMBAH DAN PENAMBAHAN NA-CMC TERHADAP KUALITAS VELVA SAYURAN ) (Jurnal Teknologi Pangan, 2013)
Velva  is a  kind  of  freezing  food,  like  ice  cream  that made  from  various  fruit  or vegetables. The materials is mixed, homogenized, cooling in the ice cream maker and than was freezed. Carrot,  tomato  and  mungbean  sprout are once  of  tropical  vegetables  can  be  used  as materials for producing velva. The research is aimed to know effect of proportion carrot, tomato,mungbean sprout and concentration of Na – CMC  to quality of velva sayuran. The Research used Complete Design Randomized with factorial pattern. The First factor is  kind  of  vegetables  (carrot,  tomato,  and  mungbean  sprout);  the    second  factor  is concentration  of  Na – CMC : 0,5%;  0,6%;  0,7  %;  0,8%;).  Ducan't  Multiple  Range  Test was used to know defference of every treatment. The  best  proportion  on  processing  velva  vegetables  is  80  :  80  :  40(carrot,  tomato  and mungbean sprout) and Na- CMC 0,8 %. This treatment is giving the highest overrun is 20,495 %;  smooth  texture  and the  highest hedonic  value  (taste  and  aroma).  The  result  of  chemical  analysis showed  that Aw 68,95 %, Caroten total 59,89 %, Vitamin C 68,39%, Vitamin E 24,33 % and Total Soluble Solid 32,47 %.Key Word : Velva Vegetables, Carrot, Tomato, Mungbean Sprout And Na - CMC